Evaluasi Model CIPP terhadap Metode Pembelajaran Mentoring pada Mata Pelajaran Pemesinan Bubut Dasar di SMK PGRI 3 Kota Malang - Ikhtarul Bagus Hylmiawan; Didik Nurhadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study was motivated by the challenge of transferring precise technical skills in the Basic Lathe Machining course at vocational high schools. The purpose of this study was to evaluate the effectiveness of the mentoring learning method at SMK PGRI 3 in Malang using the CIPP (Context, Input, Process, Product) evaluation model. The methodology employed was quantitative descriptive with an evaluative design, involving the entire population of 96 10th-grade Machining Technology students through saturated sampling. The research instrument consisted of a validated Likert-scale questionnaire, analyzed using descriptive statistics. The results indicate that all evaluation dimensions fall into the “highly effective” category, with average scores ranging from 3.48 to 3.55. The most critical finding lies in the product dimension, where the indicator of student independence in using machinery recorded the highest score (3.56), demonstrating the mentoring method’s success in fostering practical autonomy. However, in the process dimension, there is a need to optimize access to mentor consultations to level the playing field regarding students’ learning pace. In conclusion, the mentoring method is an adaptive and accelerative pedagogical strategy for enhancing students’ manufacturing competencies. This study recommends standardizing the mentor-student ratio to ensure more consistent and equitable technical monitoring quality in line with industry standards.